Acute myeloid leukemia presenting as a spontaneous hemotympanum: A Case Report and review of the literature - Rohini R. Bahethi; Eliezer Kinberg; Sarah Kidwai; Maura Cosetti; George Wanna; Enrique Perez (Otolaryngology Case Reports, 2020)
Objective: To present a unique cause of spontaneous unilateral hemotympanum. Case report: We present the case of a 71-year-old male with known history of acute myeloid leukemia (AML) who presented for evaluation of one month of aural fullness. The patient denied worsening of baseline hearing, otorrhea, or tinnitus but did endorse brief episodic vertigo that resolved without intervention. He also denied history of head trauma. Physical exam revealed unilateral hemotympanum. There were no cranial nerve deficits. There was incidental note of an infectious appearing subdural collection on a CT temporal bone obtained for further evaluation of the hemotympanum. Therefore, the patient underwent combined mastoidectomy and temporal craniotomy. Cytopathology demonstrated leukemic infiltrates and no evidence of active infection. Conclusions: Chloroma, extra-medullary deposition of leukemic cells, has rarely been reported in the temporal bone. We report a rare instance of temporal bone chloroma which presented as spontaneous hemotympanum. In the absence of an explanatory cause of hemotympanum, leukemic blast crisis resulting in chloroma can be considered.